The Role of the IMF : Financing and Its Interactions with Adjustment and Surveillance - Mussa, Michael (Pamphlet Series; Pamphlet Series, ;, 1996)
Against the background of the changing international economic environment, this pamphlet examines the general rationale for IMF financial support and the relationship between such support and IMF surveillance in carrying out the IMF's responsibility to seek to avoid and help to correct maladjustments in countries balance of payments. It analyzes the circumstances in which IMF financing continues to have an important role, draws possible lessons for the role of the IMF from the Mexican financial crisis, and discusses the future need for IMF resources.